Entrepreneurship in Latin America : A Step Up the Social Ladder? - Lora, Eduardo; Castellani, Francesca (Washington, DC: Inter-American Development Bank and the World Bank, 2013)
This book looks at both the potential and limits of policies to promote entrepreneurship as an important vehicle for social mobility in Latin America and the Caribbean. Who are the region's entrepreneurs? They tend to be middle-aged males with secondary and, often, tertiary education who represent only a small segment of the economically active population in the six countries considered in this book. They come from families in which a parent is, or was, an entrepreneur. In fact, a parent's occupation is more important in the decision to become an entrepreneur than a parent's wealth, income or education.